CHARACTERISTICS OF THE PENUMBRA AND HYPOPERFUSED LESIONS ON ARTERIAL SPIN LABELING PERFUSION SEQUENCES ACCORDING TO LARGE VESSEL OCCLUSION SITES IN ACUTE ISCHEMIC STROKE (Vietnam Journal of Community Medicine, 2026)
Objective: this study aims to describe arterial spin labeling (ASL) perfusion characteristics in acute ischemic stroke due to large vessel occlusion, according to the site of vascular obstruction.Subjects and Methods: We conducted a cross-sectional study on 55 patients with LVO who underwent emergency MRI including DWI, TOF-MRA, and ASL. Infarct core volume, penumbra volume, and ASL hypoperfused volume were compared across vascular occlusion sites using the Kruskal–Wallis test. Ratios of penumbra-to-core and ASL-to-core volumes were calculated to assess the extent of perfusion mismatch.Results: Infarct core volumes did not differ significantly among occlusion sites (p = 0.453). In contrast, penumbra volumes differed significantly, being largest in ICA and ICA+MCA occlusions and smallest in MCA occlusions (p = 0.030). ASL hypoperfused volume showed a borderline difference (p = 0.052). Both penumbra/core and ASL/core ratios differed significantly (p = 0.018 and 0.021), indicating greater perfusion mismatch in proximal occlusions compared with MCA occlusions.Conclusion: ASL effectively distinguishes perfusion abnormalities according to the site of vascular occlusion. ASL is a valuable non-contrast technique for identifying hypoperfused but salvageable tissue in acute stroke.
Keywords: MRI, Arterial spin labeling, Acute ischemic stroke, large vessel occlusion